OCCURRENCE OF LEAF RUST CAUSED BY PUCCINIA TRITICI-DURI ON ITALIAN BUGLOSS ( ANCHUSA AZUREA ) AS A SECONDARY HOST IN JORDAN (Journal of Plant Disease Sciences, 2025)
Italian Bugloss Mill.) is a common flowering plant native to Jordan and an important medical herb that has many pharmaceutical uses and has beautiful blue flowers that attract bees. A rust disease was found infecting many Italian Bugloss plants with high infection rate of a leaf rust disease during a field-trips in March, 2022 in Mutah, Karak Province of Jordan. The diseased plants had shown yellow to orange pustules of rust disease on their leaves that shown curled, malformed, wilted and dead. The leaves were only infected part of the diseased plant thus the disease is a leaf rust. Disease incidence was about 32% and severity ranged from 10-86%. The pustules were orange aecia round to ovoid in shape aeciospores with orange color were seen that have an average of 25 x 28 μm in size. Aceia stage was found on Italian Bugloss as a secondary host forPuccinia tritici- duri which is a leaf rust pathogen on durum wheat that is common in Mediterranean region and Jordan.
Keywords: Diagnosis, Fungal diseases, Italian bugloss, Leaf pest, Pucceimia tritici